Fuzzy logic controller for controlling ward leonard speed / Norzaine Madeni - Madeni, Norzaine (2009)
This poject is to improve the performance of ward leonard speed control system to control a DC motor. This motor was controlled by PID (proportional integral derivative controller). Under the conventional method, the performance of PID is slow to pick up the speed hence the ward leonard, fuzzy logic controller (FLC) is used to replace PID controller. This project has benefited many industrials and businesses like multi-expert decision making, due to its advantageous, which range from very small, micro controller based systems in home appliances to large-scale process control systems.